Effect of CYP2C19 genetic variants on bleeding and major adverse cardiovascular events in a cohort of Arab patients undergoing percutaneous coronary intervention and stent implantation. Issue 5 (7th April 2022) - Ali, Zainab Omer; Bader, Loulia; Mohammed, Shaaban; Arafa, Salaheddin; Arabi, Abdulrahman; Cavallari, Larisa; Langaee, Taimour; Mraiche, Fatima; Rizk, Nasser; Awaisu, Ahmed; Shahin, Mohamed H.; Elewa, Hazem
Abstract : Introduction: One-third of patients have clopidogrel resistance that may lead to major adverse cardiac events (MACEs). By contrast, it was found that some clopidogrel-treated patients have hyperresponsive platelets that are associated with higher bleeding risk. Several studies have shown that polymorphisms in the gene encoding the CYP2C19 contribute to the variability in response to clopidogrel. Data on genetic and nongenetic factors affecting clopidogrel response in the Arab population are scarce. In this prospective cohort study, we sought to assess the association between the increased function allele (CYP2C19*17) and bleeding events, and validate the effect of the CYP2C19 genetic variants and nongenetic factors on the incidence of MACEs. Methods: Blood samples were collected from patients that were undergoing percutaneous coronary intervention and receiving clopidogrel at the Heart Hospital, a specialist tertiary hospital in Doha, Qatar. Patients were followed for 12 months. Genotyping was performed for CYP2C19*2, *3, and *17 using TaqMan assays. Results: In 254 patients, the minor allele frequencies were 0.13, 0.004, and 0.21 for *2, *3, and *17, respectively. Over a 12-month follow-up period, there were 21 bleeding events (8.5 events/100 patient-year). CYP2C19*17 carriers were found to be associated with increased risk of bleeding (OR, 21.6; 95% CI, 4.8–96.8; P < 0.0001). CYP2C19*2 or * 3 carriers were found to be associated with increased risk of baseline and incident MACE combined (OR, 8.4; 95% CI, 3.2–23.9; P < 0.0001). Conclusion: This study showed a significant association between CYP2C19*17 allele and the increased risk of bleeding, and CYP2C19*2 or *3 with MACE outcomes.